If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 12 = -3x + -6 Reorder the terms: 12 + 5x = -3x + -6 Reorder the terms: 12 + 5x = -6 + -3x Solving 12 + 5x = -6 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 12 + 5x + 3x = -6 + -3x + 3x Combine like terms: 5x + 3x = 8x 12 + 8x = -6 + -3x + 3x Combine like terms: -3x + 3x = 0 12 + 8x = -6 + 0 12 + 8x = -6 Add '-12' to each side of the equation. 12 + -12 + 8x = -6 + -12 Combine like terms: 12 + -12 = 0 0 + 8x = -6 + -12 8x = -6 + -12 Combine like terms: -6 + -12 = -18 8x = -18 Divide each side by '8'. x = -2.25 Simplifying x = -2.25
| -7(x+4)-45=5-22 | | -14+x=x+29 | | 3y=3(6.68)-3 | | .25(-x+8)=-2+2x | | 12=5y-25 | | 7n+14=-2n+50 | | 8a+5c=3369 | | 6x-1-3=4 | | 0.5+0.25=2.00 | | Ln(x+3)+Ln(2)=Ln(16) | | ln(30x)=y | | lx+2l+lx-2l=0 | | 1/2x+6=1/6 | | 98=m-(-78) | | 3(x+6)=7x-10x+1 | | 1/3r+1/5r=8 | | .25(-8+8x)=-2+2x | | -3w+4-w-17= | | 6x-1=-3x+13 | | 5(-x+9)-8=-19 | | 72=4x+4(-3x+2) | | -8=-(x+10) | | 6(n+8)=5(n+-4) | | 0.5+6.0y=8.0 | | 8y+4(2+y)=3(y-5)+10y | | 4x+5=-1/3x-8 | | 4x-153=47-6x | | 4/5(x-8)=-12 | | 18=b+3+4b | | x(4x-3)=(4x+6)(x-3) | | (2x-y)(4x^2+2xy+y^2)= | | -32+4x=9x+13 |